Correction: Kuklane et al. A Database of Static Thermal Insulation and Evaporative Resistance Values of Dutch Firefighter Clothing Items and Ensembles. Biology 2022, 11, 1813 - Kalev Kuklane; Jakob Eggeling; Maurice Kemmeren; Ronald Heus (Biology)
The original publication contained an erroneous data line in Appendix A, “Table A1 [...]